APPLICATION OF HARDSHIP RULE UNDER THE UNIDROIT PRINCIPLES OF INTERNATIONAL COMMERCIAL CONTRACTS IN INDONESIA - Fikri Farokhi. Skd; Sanusi Sanusi (Student Journal of International Law, 2022)
This article examines the concept of hardship rule based on the UNIDROIT Principles of International Commercial Contracts (hereinafter called UPICC) and how it compares with force majeure regulated by the Indonesian Civil Code (hereinafter called ICC), as well as to analyze how it is applied in the Indonesian court decisions. This study uses a normative legal research method. The study shows that the meaning of the hardship rule under the UPICC is an event that has fundamentally changed the balance of a contract, resulting in a very high implementation value for the party performing, or the value of the implementation of the agreement is drastically reduced for the receiving party. Hardship and force majeure both occur in circumstances that preclude the obligation to perform that cannot be anticipated in advance, and the fault of either party does not cause the situation. The hardship rule emphasizes changes in circumstances by one of the parties to the contract caused by the contract value that changes significantly, causing significant losses for one of the parties, and hardship offers renegotiation for the parties. Meanwhile, force majeure is emphasized when the parties are unable to carry out all or part of the agreed performance which is generally caused by natural and social events, and force majeure offers contract suspension and termination of the contract. Indonesia has implicitly implemented this hardship in the legal system by referring to the principle of justice.